Piriformospora indica enhances growth and salt tolerance in a short rotation woody crop, Paulownia elongata, under NaCl stress - Mu, Deyu; Zhang, Meng; Liang, Yu; Ding, Chen; Chen, Qinglei; Fan, Xiaoli; Meng, Xiang; Zhang, Xinpeng; Gao, Shengyu; Zhai, Datong; Gao, Yubo; Wu, Yawei (Frontiers in Plant Science, 2025)
Salinization is a major environmental challenge that jeopardizes productivity and resilience of plants such as the short rotation woody crops (SRWC) and bioenergy crops. Leveraging beneficial microbes will enhance plant resistance to salinity with physiological adjustments. Here we investigated the efficacy of plant growth promoting fungus (Piriformospora indica) on optimizing growth and salt tolerance of SRWCs and bioenergy tree crops, using Paulownia elongata as an example. Following culture in sterile soil, the chlamydospore of P. indica were found in paulownia plants roots. We treated both inoculated and uninoculated plants with four salt concentrations (0.00%, 0.30%,0.50%, 0.70%) by soaking them in varying concentrations of NaCl solution every 7 days. After 30 days of treatment, we investigated various physiological parameters, i.e., biomass, infection rate, growth rate, photosynthetic parameters, antioxidant enzyme activity, and soluble sugar of paulownia plants. Our two-way ANOVA demonstrated that the interaction between salinity stress and P. indica inoculation significantly enhanced plant height growth rate, leaf net photosynthetic rate, superoxide dismutase (SOD) activity, and soluble protein content in Paulownia seedlings. Inoculated plants exhibited improved salt tolerance due to the mitigating effect of symbiosis across a salinity gradient. Mortality in the P. indica-treated group was reduced by approximately 5.55%, 22.22%, and 27.77% under 0.30%, 0.50%, and 0.70% NaCl treatments. Our study is the first application of P. indica to enhance salinity tolerance in Paulownia, a short-rotation woody crop. Inoculating such endophyte significantly improves the resilience and productivity of Paulownia plantations in saline environments, for a sustainable afforestation effort.